Resveratrol: Perspectives from Ethnobotanical Uses to Health Applications - Martinez-Salinas, J; Rios-Ramirez, M; Jaimes-Fernandez, L (CRC Press, 2023)
Resveratrol, one of the best known secondary plant metabolites, has attracted the attention of researchers and pharmaceutical companies thanks to its anti-oxidant properties and anti-inflammatory properties. Especially the covid 19 pandemic, which broke out in 2019, started to draw the attention of researchers to many plant-derived active substances, especially resveratrol. In fact, its effectiveness has been tested with experimental studies, such as lung fibrosis, chronic obstructive pulmonary disease, cancer and asthma on resveratrol, whose effectiveness in covid-19 has not been fully clarified. Many researchers based on these studies have added their own comments along with reviews about resveratrol. However, few of them mentioned the full side effects of resveratrol. Despite all this, the effectiveness of resveratrol against covid-19 is still not investigated. Because covid-19 is at risk of over-contamination, it requires extraordinary laboratory conditions for researchers. The fact that both the world health organization and local legislators allow researchers under limited conditions continues to contribute to the continued uncertainty of the relationship between covid-19 and resveratrol. © 2023 José L. Martinez, Alfred Maroyi and Marcelo L. Wagner.